Collegiate Grading Practices and the Gender Pay Gap - Dowd, Alicia C. (Education Policy Analysis Archives, 2000)
Extending research findings by R. Sabot and J. Wakeman-Linn (1991), this article presents a theoretical analysis showing that relatively low grading quantitative fields and high grading verbal fields create a disincentive for college women to invest in quantitative study. Pressures on grading practices are modeled using higher education production functions.